Pengaruh Likuiditas, Leverage, Sales Growth, Solvabilitas, Dan Profitabilitas Terhadap Financial Distress - Siti Suharni; Arini Wildaniyati; Ratna Dyah Puspaningrum (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of liquidity, leverage, sales growth, solvency, and profitability on financial distress in manufacturing companies in the textile and garment sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. Financial distress is an unhealthy financial condition that can lead to bankruptcy, making it crucial to understand the factors that influence it. This research employs a quantitative method using multiple regression analysis. The data used are secondary data obtained from the annual financial reports of the sampled companies. The independent variables in this study are liquidity (current ratio), leverage (debt to equity ratio), sales growth, solvency (debt to asset ratio), and profitability (return on assets), while the dependent variable is financial distress measured using the Altman Z-Score model.The results of the t-test show that the liquidity variable partially has a significant effect on financial distress, leverage partially has a significant effect on financial distress, sales growth partially has no significant effect on financial distress, solvency partially has no significant effect on financial distress, and profitability partially has no significant effect on financial distress. Meanwhile, the F-test results indicate that liquidity, leverage, sales growth, solvency, and profitability simultaneously have a significant effect on financial distress.